Chasing the rainbow: pleasure, sex-based sociality and consumerism in navigating and exiting the Irish Chemsex scene. Issue 9 (2nd September 2019) - Van Hout, Marie Claire; Crowley, Des; O'Dea, Siobhan; Clarke, Susan
Abstract: Club drug use among gay, bisexual and other men who have sex with men is increasingly normalised within sexual contexts and is associated with increased sexual risk behaviours. The term Chemsex is used to describe sexualised drug use lasting several hours or days with multiple sexual partners. A small pilot study, underpinned by interpretative phenomenological analysis (IPA), was conducted in Dublin, Ireland. Interviews were conducted with 10 men who were experiencing physical and emotional health problems as a consequence of their participation in sexualised drug use and wished to exit the Chemsex scene. Interviews explored experiences of sexualised drug use, motives to partake, the organisation of Chemsex parties and group connectivity, drugs used, harm reduction, pleasure and consequences of participation over time. Four basic themes emerged from the analysis: social and cyber arrangements within the Dublin Chemsex scene; poly drug use and experiences of drug dependence; drug and sexual harm reduction within the Chemsex circle of novices and experts; and sexualised drug use, escapism and compulsive participation. Two higher-order themes were also apparent: first, the reinforcing aspects of drug and sexual pleasure; and second, the interplay between excess drug consumption and sex, and drug dependence.